Resonances in QCD - Lutz, Matthias F. M.; Lange, Jens Sören; Pennington, Michael; Bettoni, Diego; Brambilla, Nora; Crede, Volker; Eidelman, Simon; Gillitzer, Albrecht; Gradl, Wolfgang; Lang, Christian B.; Metag, Volker; Nakano, Takashi; et al. (Nuclear physics. A, Nuclear and hadronic physics, 2016)
We report on the EMMI Rapid Reaction Task Force meeting ‘Resonances in QCD’, which took place at GSI October 12-14, 2015. A group of 26 people met to discuss the physics of resonances in QCD. The aim of the meeting was defined by the following three key questions:•What is needed to understand the physics of resonances in QCD?•Where does QCD lead us to expect resonances with exotic quantum numbers?•What experimental efforts are required to arrive at a coherent picture? For light mesons and baryons only those with up, down and strange quark content were considered. For heavy-light and heavy-heavy meson systems, those with charm quarks were the focus. This document summarizes the discussions by the participants, which in turn led to the coherent conclusions we present here.
Gesehen am 20.05.2020